An atom-economical addition of methyl azaarenes with aromatic aldehydes via benzylic C(sp3)–H bond functionalization under solvent- and catalyst-free conditions - Yennamaneni, Divya Rohini; Amrutham, Vasu; Gajula, Krishna Sai; Banothu, Rammurthy; Boosa, Murali; Nama, Narender (Beilstein Journal of Organic Chemistry, 2020)
A convenient practical approach for the synthesis of 2-(pyridin-2-yl)ethanols by direct benzylic addition of azaarenes and aldehydes under catalyst- and solvent-free conditions is reported. This reaction is metal-free, green, and was carried out in a facile operative environment without using any hazardous transition metal catalysts or any other coupling reagents. Different aromatic aldehydes and azaarenes were monitored, and the yields of the resulting products were moderate to excellent. We accomplished several azaarene derivatives under neat conditions through a highly atom-economical pathway. To evaluate the preparative potential of this process, gram-scale reactions were performed up to a 10 g scale.
Keywords: aldehydes; azaarenes; benzylic addition; green chemistry; solvent-free conditions

(untitled) - Chelucci, G.; Orrù, G.; Pinna, G. A. (Tetrahedron, 2003)

(untitled) - Prehn, K.; Warburg, A.; Schilling, T.; Bron, M.; Schulte, K. (Compos. Sci. Technol., 2009)

(untitled) - Kem, W. R.; Soti, F.; Rittschof, D. (Biomol. Eng., 2003)

(untitled) - Friesen, R. W.; Brideau, C.; Chan, C. C.; Charleson, S.; Deschênes, D.; Dubé, D.; Ethier, D.; Fortin, R.; Gauthier, J. Y.; Girard, Y.; Gordon, R.; Greig, G. M.; et al. (Bioorg. Med. Chem. Lett., 1998)

(untitled) - Capdeville, R.; Buchdunger, E.; Zimmermann, J.; Matter, A. (Nat. Rev. Drug Discovery, 2002)

(untitled) - Solomon, V. R.; Lee, H. (Curr. Med. Chem., 2011)

(untitled) - Wilson, K. J.; van Niel, M. B.; Cooper, L.; Bloomfield, D.; O’Connor, D.; Fish, L. R.; MacLeod, A. M. (Bioorg. Med. Chem. Lett., 2007)

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2005)

The Alkaloids - Strunz, G. M.; Findlay, J. A. (Pyridine and Piperidine Alkaloids, 1985)

(untitled) - Meth-Cohn, O.; Yau, C. C.; Yu, C.-Y. (J. Heterocycl. Chem., 1999)

(untitled) - Houghton, P. J.; Woldemariam, T. Z.; Watanabe, Y.; Yates, M. (Planta Med., 1999)

(untitled) - Kumar, S.; Bawa, S.; Gupta, H. (Mini-Rev. Med. Chem., 2009)

(untitled) - Fournet, A.; Barrios, A. A.; Muñoz, V.; Hocquemiller, R.; Roblot, F.; Cavé, A.; Richomme, P.; Bruneton, J. (Phytother. Res., 1994)

(untitled) - Nakamura, I.; Yamamoto, Y. (Chem. Rev., 2004)

(untitled) - Campeau, L.-C.; Rousseaux, S.; Fagnou, K. (J. Am. Chem. Soc., 2005)

(untitled) - Kanyiva, K. S.; Nakao, Y.; Hiyama, T. (Angew. Chem., Int. Ed., 2007)

(untitled) - Wu, J.; Cui, X.; Chen, L.; Jiang, G.; Wu, Y. (J. Am. Chem. Soc., 2009)

(untitled) - Mousseau, J. J.; Bull, J. A.; Charette, A. B. (Angew. Chem., Int. Ed., 2010)

(untitled) - Deng, G.; Ueda, K.; Yanagisawa, S.; Itami, K.; Li, C.-J. (Chem. – Eur. J., 2009)

(untitled) - Tobisu, M.; Hyodo, I.; Chatani, N. (J. Am. Chem. Soc., 2009)

(untitled) - Qian, B.; Guo, S.; Shao, J.; Zhu, Q.; Yang, L.; Xia, C.; Huang, H. (J. Am. Chem. Soc., 2010)

(untitled) - Qian, B.; Xie, P.; Xie, Y.; Huang, H. (Org. Lett., 2011)

(untitled) - Jazzar, R.; Hitce, J.; Renaudat, A.; Sofack-Kreutzer, J.; Baudoin, O. (Chem. – Eur. J., 2010)

(untitled) - Lyons, T. W.; Sanford, M. S. (Chem. Rev., 2010)

(untitled) - Kalyani, D.; Deprez, N. R.; Desai, L. V.; Sanford, M. S. (J. Am. Chem. Soc., 2005)

(untitled) - Shabashov, D.; Daugulis, O. (Org. Lett., 2005)

(untitled) - Mao, D.; Hong, G.; Wu, S.; Liu, X.; Yu, J.; Wang, L. (Eur. J. Org. Chem., 2014)

(untitled) - Yaragorla, S.; Dada, R.; Singh, G. (Synlett, 2016)

(untitled) - Yaragorla, S.; Singh, G.; Dada, R. (Tetrahedron Lett., 2016)

(untitled) - Wang, F.-F.; Luo, C.-P.; Wang, Y.; Deng, G.; Yang, L. (Org. Biomol. Chem., 2012)

(untitled) - Nageswara Rao, N.; Meshram, H. M. (Tetrahedron Lett., 2013)

(untitled) - Percino, M. J.; Chapela, V. M.; Cerón, M.; Soriano-Moro, G.; Castro, M. E. (Res. Chem. Intermed., 2015)

(untitled) - Zhang, X.-Y.; Dong, D.-Q.; Yue, T.; Hao, S.-H.; Wang, Z.-L. (Tetrahedron Lett., 2014)

(untitled) - Wang, Z.-L. (RSC Adv., 2015)

(untitled) - Yaragorla, S.; Singh, G.; Dada, R. (Tetrahedron Lett., 2015)

(untitled) - Chen, Z.; Luo, M.; Wen, Y.; Luo, G.; Liu, L. (Org. Lett., 2014)

(untitled) - Nallasivam, J. L.; Fernandes, R. A. (Eur. J. Org. Chem., 2015)

(untitled) - Sharma, R.; Abdullaha, M.; Bharate, S. B. (J. Org. Chem., 2017)

(untitled) - Latha, D. S.; Yaragorla, S. (Eur. J. Org. Chem., 2020)

Green Chemical Syntheses and Processes - Anastas, P. T.; Heine, L. G.; Williamson, T. C. (Oxford University Press, 2000)

Green chemistry: theory and practice - Anastas, P. T.; Warner, J. C. (Oxford University Press, 1998)

Green chemistry: challenging perspectives - Varma, R. S. (Oxford University Press, 2000)

(untitled) - Xu, L.; Shao, Z.; Wang, L.; Zhao, H.; Xiao, J. (Tetrahedron Lett., 2014)

(untitled) - Malviya, B. K.; Singh, K.; Jaiswal, P. K.; Shukla, M.; Verma, V. P.; Vanangamudi, M.; Jassal, A. K.; Punjabi, P. B.; Sharma, S. (ACS Omega, 2019)

Catalyst-free Organic Synthesis - Goutam, B. (Royal Society of Chemistry, 2017)

(untitled) - Rao, Y. S.; Latha, D. S.; Devunuri, N.; Almansour, A. I.; Arumugam, N.; Yaragorla, S. (Eur. J. Org. Chem., 2020)